Current status of oilseed crops in the Republic of Kazakhstan - Didorenko Svetlana; Kassenov Rinat; Kisetova Elmira; Bayzhanov Zhasulan; Kushanova Rystay (Oilseeds and fats, crops and lipids)
The global production of oilseed crops is a rapidly evolving sector. Soybean, rapeseed, sunflower, and cotton hold the leading positions among oilseed crops. Among technical oils, linseed oil ranks first. In the Republic of Kazakhstan, cultivated areas dedicated to oilseed crops cover approximately 2.5 to 3 million hectares. Sunflower, flax, and rapeseed account for 75% of the total sown area, primarily concentrated in the northern regions of the country. Soybean, grown on irrigated plots, and safflower, cultivated in rainfed areas, are expanding in the south of Kazakhstan. The number of foreign varieties and hybrids of oilseed crops included in the State Register of recommended crops in Kazakhstan is updated annually. For 2024, the register includes 124 sunflower hybrids, 56 soybean varieties, 45 rapeseed hybrids, 9 flax varieties, and 2 safflower varieties. The national breeding programme for oilseed crops is conducted by 10 scientific institutions. Between 2015 and 2024, 18 domestic varieties and hybrids of sunflower, 16 varieties of soybean, 5 of rapeseed, 3 of flax, and 2 of safflower were approved for production in Kazakhstan.